Comparison of Clinical Characteristics of Patients on whom Electroconvulsive Therapy was Applied as Inpatient and Outpatient. Issue 1 (1st March 2016) - Demir, Suleyman; Bulut, Mahmut; Atli, Abdullah; Gunes, Mehmet; Kaya, Mehmet Cemal; Ibiloglu, Aslihan Okan; Cati, Songul; Sir, Aytekin
ABSTRACT: Objective : Electroconvulsive therapy (ECT) is an efficient and reliable somatic treatment used to treat severe mental disorders. ECT procedure is generally performed by hospitalizing the patient in our country (Turkey). However, there is no obligation to perform ECT by hospitalization, as ECT may be performed without hospitalizing the patient. Outpatient ECT gradually increases during acute and maintenance treatment. Outpatient ECT provides some advantages, such as reduced disruption in social and professional functionality and decrease in treatment costs. Studies that compare acute outpatient ECT and ECT applied after hospitalization are limited. In the present study, we aimed to review clinical characteristics of acute ambulatory ECT and ECT applied by hospitalization comprehensively and retrospectively. Methods : Inpatients and outpatients that received ECT in the Psychiatry Clinic of Dicle University between 2011 and 2014 were enrolled in the present study. Patients' files between aforementioned years were reviewed retrospectively and data including patient age, gender, diagnosis according to DSM system, hospitalization period, whether ECT was applied, number of ECT sessions, and whether ECT was performed as an inpatient or outpatient procedure were recorded. For the patients who were hospitalized multiple times, each hospitalization was regarded as a different patient and data were assessed independently. For the outpatients who received ECT, all separate ECT sessions were added and ECT count was determined. Those who received maintenance ECT sessions were not included in the outpatient ECT group. Patients who received ECT by acute referral as outpatients were included in this group. Results : Between 2011 and 2014, 904 patients were admitted to the Psychiatry Clinic of Dicle University, Faculty of Medicine, of which 138 received ECT treatment. We also included in the study an additional 38 outpatients who received acute ECT. Inpatients of our clinic in application to ECT were rates of 15.3%. There was no statistically significant difference detected between age, number of ECT sessions applied, diagnosis, and gender of admitted inpatients and outpatients (p<0.05). Conclusions : In our study clinical characteristics of inpatients and outpatients subjects who admitted in order to practiced the ECT were determined to be similar. We believe that an efficient treatment method may be presented to the patients by including acute outpatient ECT more frequently in the treatment plan from physicians.